PENYUSUNAN LAPORAN KEUANGAN USAHA MIKRO KECIL MENENGAH LAUNDRY SEPATU SEPASANG BERDASARKAN SAK EMKM - Ahmad Ridho Dwiseno; Muhammad Abdul Muis; Suwardi Suwardi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
This study aims to compile financial reports based on SAK EMKM with the research object of Laundry Sepatu Sepasang, namely one of the MSMEs domiciled in Malang City. The research methodology used is a qualitative method with a descriptive qualitative approach. The type of data used in this research is primary data. Primary data is data obtained directly from the object of writing and obtained through an interview or question and answer process on a list of questions that the author has prepared. The source of the data in writing this final project is data that the writer obtained directly from the owner of MSME Shoes Laundry Sepasang as the object of research. The results of this study indicate that the research object has not prepared financial reports that are in accordance with SAK EMKM. Meanwhile, in general, the recording is only limited to cash receipts and disbursements. MSME Shoes Laundry Sepasang also experienced several obstacles so that the presentation of financial reports was hampered, while based on SAK EMKM had to present three financial reports, namely Statements of Financial Position, Statements of Profit or Loss, and Notes to the Financial Statements.